2017
DOI: 10.1002/capr.12157
|View full text |Cite
|
Sign up to set email alerts
|

Integrating diversity into therapy processes: The role of individual and cultural diversity competences in promoting equality of care

Abstract: Background One of the most significant challenges facing the provision of health care in present societies is the fact that the largest growing segment of the patient population is comprised of individual and culturally diverse people. However, the impact of this diversity on clinician–client interactions has only been examined recently. This study addresses the issues of culture and diversity in psychotherapy processes in Portugal. Methods The study used an analogue experimental design, in a qualitative analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Conversely, the lower scoring by both parties on items related to evaluation and practice of skills and higher allocation of ‘not applicable to my practice’ (N/A) to the item ‘addresses cultural diversity…’ may highlight some limitations in the current understanding, awareness and training in the breadth of skills supervisors need to be practicing in supervision (Falender & Shafranske, 2014). For instance, while there is growing agreement that cultural diversity capability and multi‐cultural competence carries significant weight in influencing the supervisory working alliance, outcomes of goals and tasks and conceptualisation of case work (King, Borders, & Jones, 2020; Moleiro, Freire, Pinto, & Roberto, 2018), our findings suggest that this area of supervisor competency requires greater focus. Enhancing the translation of cultural competency skills into regular practice through evidenced‐based supervisor training is vital (Kissil, Davey, & Davey, 2013), and is a skill that should be predominantly facilitated by the supervisor (King et al., 2020; Kissil et al., 2013).…”
Section: Discussionmentioning
confidence: 62%
“…Conversely, the lower scoring by both parties on items related to evaluation and practice of skills and higher allocation of ‘not applicable to my practice’ (N/A) to the item ‘addresses cultural diversity…’ may highlight some limitations in the current understanding, awareness and training in the breadth of skills supervisors need to be practicing in supervision (Falender & Shafranske, 2014). For instance, while there is growing agreement that cultural diversity capability and multi‐cultural competence carries significant weight in influencing the supervisory working alliance, outcomes of goals and tasks and conceptualisation of case work (King, Borders, & Jones, 2020; Moleiro, Freire, Pinto, & Roberto, 2018), our findings suggest that this area of supervisor competency requires greater focus. Enhancing the translation of cultural competency skills into regular practice through evidenced‐based supervisor training is vital (Kissil, Davey, & Davey, 2013), and is a skill that should be predominantly facilitated by the supervisor (King et al., 2020; Kissil et al., 2013).…”
Section: Discussionmentioning
confidence: 62%
“…Our critical review also showed that sexual orientation and class issues were under-conceptualized in studies examining cultural differences in therapy dyads. We found that clients of culturally dominant groups (e.g., heterosexual upper-middle-class men) were rarely perceived as cultural; culture in therapy is positioned as solely linked to the marginalized groups of clients (Moleiro et al, 2018). Despite the importance of clinicians' self-reflection and capacity to discuss these differences and potential clinical ruptures (Goettsche, 2015), process-oriented psychotherapy research in cross-cultural encounters found that therapists do not often intentionally start conversations with clients about cultural issues (Lee & Horvath, 2013.…”
Section: Discussionmentioning
confidence: 82%
“…It is also noteworthy that all, except six, analyzed samples of actual therapy participants who were in therapy or recent clients at the time of data collection. The other six studies that did not sample actual therapy participants (Burkard et al, 1999(Burkard et al, , 2003LeVine & Franco, 1983;Moleiro et al, 2018;Naser, 2019;Ridley, 1986) used analog methods recruiting volunteers (e.g., undergraduate or graduate students) who participated in a study to watch simulated case materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they pinpoint a series of factors reported by economically disadvantaged clients which act as barriers to effective treatment; geographical and financial impediments to access health centres, culturally bound prejudices and stigma surrounding mental health problems, and a perceived ‘clash’ of perspectives that may leave clients feeling misunderstood. The theme of cultural diversity is also approached by Moleiro () through a detailed examination of psychotherapists’ cultural awareness and competency, where they were interviewed after being presented with two video vignettes of clients from minority social groups (according to migration status, ethnicity and religious affiliation) and two control vignettes of college students presenting the same complaints. With reference to a range of established multicultural competency frameworks, Moleiro concluded that the majority (70.5%) of rated answers from participants reflected low levels of cultural competency across the domains of openness to differences/attitude, awareness, knowledge and skills.…”
mentioning
confidence: 99%